Exceptional longevity and muscle and fitness related genotypes: a functional in vitro analysis and case-control association replication study with SNPs THRH rs7832552, IL6 rs1800795, and ACSL1 rs6552828 - Fuku, Noriyuki; He, Zi-hong; Sanchis-Gomar, Fabian; Pareja-Galeano, Helios; Tian, Ye; Arai, Yasumichi; Abe, Yukiko; Murakami, Haruka; Miyachi, Motohiko; Zempo, Hirofumi; Naito, Hisashi; Yvert, Thomas; et al. (Frontiers in Aging Neuroscience, 2015)
There are several gene variants that are candidates to influence functional capacity in long-lived individuals. As such, their potential association with exceptional longevity (EL, i.e., reaching 100+ years) deserves analysis. Among them are rs7832552 in the thyrotropin-releasing hormone receptor (TRHR) gene, rs1800795 in the interleukin-6 (IL6) gene and rs6552828 in the coenzyme A synthetase long-chain 1 (ACSL1) gene. To gain insight into their functionality (which is yet unknown), here we determined for the first time luciferase gene reporter activity at the muscle tissue level in rs7832552 and rs6552828. We then compared allele/genotype frequencies of the 3 abovementioned variants among centenarians [n=138, age range 100-111 years (114 women)] and healthy controls [n=334, 20-50 years (141 women)] of the same ethnic and geographic origin (Spain). We also studied healthy centenarians [n=79, 100-104 years (40 women)] and controls [n=316, 27-81 years (156 women)] from Italy, and centenarians [n=742, 100-116 years (623 women)] and healthy controls [n=499, 23-59 years (356 women)] from Japan. The THRH rs7832552 T-allele and ACSL1 rs6552828 A-allele up-regulated luciferase activity compared to the C and G-allele, respectively (P≤0.001). Yet we found no significant association of EL with rs7832552, rs1800795 or rs6552828 in any of the 3 cohorts. Further research is needed with larger cohorts of centenarians of different origin as well as with younger old people.